Acute Urinary Retention in Pregnancy - Vernekar Ritesh2, R.B. Nerli 1, S.B. Alur 1, M.B. Hiremath1, Prabha Vikram1* (Recent Research in Science and Technology, 2010)
Acute urinary retention in pregnancy due to retroverted gravid uterus is uncommon and an emergency condition. We present 2 such cases of acute urinary retention in pregnancy. Both the patients had retroverted uterus. This condition is most common in 1st trimester of pregnancy. Its low incidence and little published evidence often lead to suboptimal management. Successful management has been reported either by replacement of uterus in anterior position or by internal drainage of bladder. Keywords: Urinary retention, pregnancy, urethral obstruction